Metode Pembelajaran Pendidikan Agama Kristen untuk Orang Dewasa di Gereja Pada Era Digital dan Pandemi Covid-19 - Daniel Darmawan; Windy Daud; Aliyono; Desi Sianipar (UKI Press, 2023)
The digital era and the Covid-19 pandemic are a challenge for adults. If they adjust wrongly to it, then it will affect all aspects of their lives. The church needs to serve them by implementing Christian religious education. However, Christian religious education must be delivered with the proper learning methods. Church educators must use the learning methods in responding to the challenges and needs of adults. The purpose of this study is to give ideas about the learning methods for adults. The type of research used is qualitative research that uses a library research approach. The result of the research is teachers in the churches can use the Forum Discussion Group (FGD), Problem-Solving, Collaborative Learning, and training to support adults in the digital era and Pandemic Covid 19.